Managing with the Changing Competitive Landscape in Malaysia’s Power Generation Market through Sustainable Innovation - Hamzah, Rosman (2014)
Today’s power generation market in Malaysia has evolved into a competitive market. In the beginning, there was no competition. The market was monopolised by a single utility. A nation-wide blackout triggered the introduction of independent power producers (IPPs) into the market in 1993. The market was transformed into an oligopoly market dominated by a few politically linked companies. These pioneering IPPs were awarded with IPP concessions without open tender. Pressured by increasing cost of fuel, the Malaysian government in recent times have decided to open the market to new players. Open tender will create competition that will eventually drive down electricity tariffs to the consumers. So, where does sustainable innovation fits into the power generation market in Malaysia? Sustainable innovation considers impact on the 3Ps; Planet, People and Profit. In the modern era where the public is demanding that the earth and its inhabitants be protected and the shareholders are demanding profit, all innovation must consider sustainability. Power generation in Malaysia has never been perceived as an innovative industry. Direct award of concessions resulted in lucrative financial returns. Long term power purchase agreement with terms favourable to the IPPs meant that the IPPs were not in any pressure to improve as long they delivered power as contracted. Generating power was business as usual. However, the market has transformed. The pioneering IPPs now have to compete not just amongst existing IPPs, but also against new players. Open tender meant the IPPs must submit the lowest levelised tariff in order to win. The concessions are no longer as lucrative as before. The PPA terms are now favouring the buyer. In order to compete, the pioneering IPPs must rid themselves of their legacies from the old market and transform their firms into competitive firms. They must innovate in order to gain competitive advantage over their rivals. All innovation initiatives by the IPPs in Malaysia must consider sustainable innovation. The main purpose of this management project (MP) is to assess whether the IPPs in Malaysia are managing with the changing competitive landscape in Malaysia’s power generation market through sustainable innovation. The MP reviewed theories and literatures to better understand innovation, its drivers, the barriers and how best to manage innovation. The MP searched for existing innovations in the power generation industry globally in order to better understand the industry. The MP expanded the study by exploring if the culture and environment in Malaysia have any influence on how the IPPs manage innovation. The MP used both qualitative and quantitative methods based on established theories in order to perform the assessments. Using two different methods enabled the MP to check for consistencies of information. Where there were inconsistencies, the MP performed in depth analysis. To gain insights that were not available from the public domain, the MP selected senior executives from those companies as subjects.